3(2x-4)=8+2x+6

Simple and best practice solution for 3(2x-4)=8+2x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-4)=8+2x+6 equation:


Simplifying
3(2x + -4) = 8 + 2x + 6

Reorder the terms:
3(-4 + 2x) = 8 + 2x + 6
(-4 * 3 + 2x * 3) = 8 + 2x + 6
(-12 + 6x) = 8 + 2x + 6

Reorder the terms:
-12 + 6x = 8 + 6 + 2x

Combine like terms: 8 + 6 = 14
-12 + 6x = 14 + 2x

Solving
-12 + 6x = 14 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-12 + 6x + -2x = 14 + 2x + -2x

Combine like terms: 6x + -2x = 4x
-12 + 4x = 14 + 2x + -2x

Combine like terms: 2x + -2x = 0
-12 + 4x = 14 + 0
-12 + 4x = 14

Add '12' to each side of the equation.
-12 + 12 + 4x = 14 + 12

Combine like terms: -12 + 12 = 0
0 + 4x = 14 + 12
4x = 14 + 12

Combine like terms: 14 + 12 = 26
4x = 26

Divide each side by '4'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| -0.75x+0.25=0.5x-0.75 | | 3x^2+11=8x | | 11/10d=2.2 | | 12n^2=-9 | | 2e-3=1 | | (4-9w)/(4w^2-49) | | 7c-5=9 | | 4x+25=19 | | 4-9w/4w^2-49 | | 11/10d=2/5 | | 48x+7.48=-5 | | 5a+1=9 | | (2x^3-3x^2-18x-8)/x-1) | | 15x-28=73 | | 18=15+5x | | 7p^2-7p-24=-5 | | 16t^2-23t-2= | | 3.3+9.8=19.04 | | 5/11g=2/3 | | n-5/n+8=2/7 | | X+68=x+128 | | 3m^2+6m-12m^2+9m= | | (2x^3+3x^2)+(5x^3+4x^2)= | | 21=3-9x | | 4v^2-12v-14=-11 | | z/1.3=.02 | | 7n+4=45 | | M^2+121=0 | | (0.25)x+2=64 | | L=34x+0.5 | | 5t^2-11t-3= | | 9+5x=-11+x |

Equations solver categories